English Vocabulary in Use. Pre-Intermediate and intermediate - Redman S. Stuart (Cambridge, Cambridge University Press, 2011)
Do you want to improve your vocabulary quickly? English Vocabulary in Use has it all. For English language learners at Bi level, this third edition of the best-selling vocabulary book now offers: Fully updated units informed by the English Vocabulary Profile, so you learn the most important words at intermediate level New words presented and explained in context Lots of opportunities for personalised practice A common mistakes feature which helps you avoid frequent errors